2022
DOI: 10.1037/cns0000344
|View full text |Cite
|
Sign up to set email alerts
|

Examining the associations between nonbelieved memories and memory distrust, self-esteem, and rumination.

Abstract: When beliefs in autobiographical memories are reduced while recollections remain relatively intact, a phenomenon termed nonbelieved memories (NBMs) unfolds. The current preregistered study (N = 104) used a 3-week longitudinal design to investigate the relationships between the frequency of recalled NBMs, memory distrust, rumination over autobiographical events, and self-esteem. Our analyses showed that memory distrust was a positive predictor for the initial recall of NBMs during the past 2 months at Time 1, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…The experience of sometimes finding it difficult to trust one’s memory is widely shared (e.g., Kuczek et al, 2018; Nash et al, 2022; Otgaar et al, 2019; van Bergen, Brands, et al, 2010; Zhang, Battista, et al, 2022). Sometimes, as a result of suggestive questioning during police interrogations, it can lead to egregious outcomes such as false confessions (i.e., memory distrust syndrome; see Gudjonsson et al, 2014; Gudjonsson & MacKeith, 1982).…”
Section: Cultural Differencesmentioning
confidence: 99%
See 2 more Smart Citations
“…The experience of sometimes finding it difficult to trust one’s memory is widely shared (e.g., Kuczek et al, 2018; Nash et al, 2022; Otgaar et al, 2019; van Bergen, Brands, et al, 2010; Zhang, Battista, et al, 2022). Sometimes, as a result of suggestive questioning during police interrogations, it can lead to egregious outcomes such as false confessions (i.e., memory distrust syndrome; see Gudjonsson et al, 2014; Gudjonsson & MacKeith, 1982).…”
Section: Cultural Differencesmentioning
confidence: 99%
“…Moreover, individuals differ in the extent to which they are more versus less skeptical toward their own memories (Nash et al, 2022; van Bergen, Brands, et al, 2010). To measure individual differences in this metamemorial appraisal, also conceptualized as trait memory distrust, van Bergen, Brands, et al (2010) adapted and validated the Squire Subjective Memory Questionnaire (SSMQ; Squire et al, 1979), which has been employed widely by subsequent research on memory distrust (e.g., Kuczek et al, 2021; Saraiva et al, 2020; van Bergen, Horselenberg, et al, 2010; Zhang, Battista, et al, 2022).…”
Section: Cultural Differencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Preprint: CHEAP-STRATEGY BIAS AND MEMORY DISTRUST If our 'unmotivated cynic' account of memory distrust is correct, then how might this account fit with prior findings that suggest memory distrusters (based on either the SSMQ or the MDS) are more likely to accept misinformation about a witnessed event (e.g. van Bergen et al, 2010b), more likely to report experiencing nonbelieved memories (Zhang et al, 2022a(Zhang et al, , 2022b, and more likely to change their memory decisions in response to feedback which falsely implies that their memories are incorrect (Zhang et al, 2023)? Perhaps the most obvious interpretation is that memory-distrusters, because of their belief that their own memories are unreliable, frequently judge that it is better to simply accept suggestions about their past experiences, rather than wasting time and effort in disputing and investigating them.…”
Section: Discussionmentioning
confidence: 83%
“…Research has shown that people who score highly on memory distrust-as measured by lower scores on the SSMQ-tend to be more susceptible to accepting misinformation about a witnessed event (van Bergen et al, 2010b, although see Kuczek et al, 2021 for a non-replication of this result) and are more likely to report experiencing nonbelieved memories (Zhang et al, 2022a(Zhang et al, , 2022b. Findings such as these point to the role of memory distrust in shaping people's attributions of and decisions about their recollections, thus indicating its relevance to the memory reconstruction process.…”
Section: Introductionmentioning
confidence: 99%